Proceedings of the 2017 International Conference on Digital Health 2017
DOI: 10.1145/3079452.3079464
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Epidemiological Models for Dengue Fever Based on Twitter Data

Abstract: Epidemiological early warning systems for dengue fever rely on upto-date epidemiological data to forecast future incidence. However, epidemiological data typically requires time to be available, due to the application of time-consuming laboratorial tests. is implies that epidemiological models need to issue predictions with larger antecedence, making their task even more di cult. On the other hand, online platforms, such as Twi er or Google, allow us to obtain samples of users' interaction in near real-time an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Most of the included studies relied on machine learning methods, particularly supervised learning models, to assess traditional and also novel data streams. These models were useful also for the analysis of traditional data sources, and allowed scientists to harness non-structured data with NLP methods [40,43,48,49,[51][52][53]56,60,65,66,[69][70][71]73,76,77,[79][80][81]84,85,92,98,100,102,105,[110][111][112]114,115,126,127,130,[134][135][136][137][138][139]. Unsupervised learning models were not the method of choice in most studies, possibly because these studies wanted to identify relevant data sources and/or indicators for dengue monitoring and prediction.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…Most of the included studies relied on machine learning methods, particularly supervised learning models, to assess traditional and also novel data streams. These models were useful also for the analysis of traditional data sources, and allowed scientists to harness non-structured data with NLP methods [40,43,48,49,[51][52][53]56,60,65,66,[69][70][71]73,76,77,[79][80][81]84,85,92,98,100,102,105,[110][111][112]114,115,126,127,130,[134][135][136][137][138][139]. Unsupervised learning models were not the method of choice in most studies, possibly because these studies wanted to identify relevant data sources and/or indicators for dengue monitoring and prediction.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…The use of the epidemiology theory is not common as it can require data that are not available through the use of IBSs owing to its limits in terms of user information (eg, age and location); however, some studies have implemented various epidemiological models [96,121,140,170], as well as epidemiological parameters [34,119].…”
Section: Research Question 3: How Are Internet-based Sources Applied mentioning
confidence: 99%
“…Existing studies have found that social media data are useful in identifying infectious disease outbreaks [12,13], analyzing sentimental reactions and responses [14,15], assessing risks [16], and understanding disease dynamics [17,18]. Before the COVID-19 pandemic, social media data have been used for multiple infectious diseases including Ebola [19,20], Zika [21,22], H1N1 [23,24], dengue [25][26][27], and seasonal influenza [28,29].…”
Section: Social Media For Human Mobility In Epidemiological Studiesmentioning
confidence: 99%
“…Geotagged social media data showed their potential in helping analyze and predict the spread of infectious diseases by deriving human mobility patterns from the data. For example, Albinati et al generated a prediction model for dengue using Twitter data [25]. Kraemer et al derived human mobility patterns from Twitter and analyzed spatiotemporal transmission variation of dengue in Lahore, Pakistan [27].…”
Section: Social Media For Human Mobility In Epidemiological Studiesmentioning
confidence: 99%